IMPROVING SPEAKING SKILL OF THE TENTH-GRADE STUDENTS OF SMAN 1 GIANYAR IN ACADEMIC YEAR 2020/2021 THROUGH TALKING CHIPS COMBINED WITH PICTURE - Vergilius Mangkar; Ni Made Wersi Murtini (Academic Journal on English Studies (AJOES), 2021)
This classroom action research is conducted to 32 subjects aims at figuring the improvement of speaking skill of the tenth-grade students of SMAN 1 Gianyar through implementing talking chips combined with picture. Talking chips is a technique of teaching speaking in this present study which have two elements such: Talk and Chips. The research was carried out through implementing talking chips combined with picture in two cycles and the obtained data was analyzed quantitatively from pre-test, post-test 1 and post-test 2; then quantitatively from questionnaire. The result showed that there was a significant improvement in the subjects’ skill in speaking descriptive monologue. Moreover, the questionnaire proved that the subjects agreed toward the implementation of talking chips combined with picture during the teaching learning process. Based on the result of the investigation, it can be concluded that the speaking skill of the tenth-grade students of SMAN 1 Gianyar in academic year 2020/2021 can be improved through talking chips combined with picture.